Penggunaan Metode Demonstrasi Dalam Meningkatkan Motivasi Belajar Matematika Siswa Kelas X IPA di SMA Negeri 1 Stabat - Hendrik; Irvan; Maradoly (LPPM STKIP AL MAKSUM, 2023)
The low motivation of students to learn resulted in low KKM scores achieved. Field facts show that many students have not achieved the set KKM scores. Therefore, the use of demonstration methods is considered as a solution to increase student learning motivation, especially in mathematics subjects at SMA Negeri 1 Stabat.This study uses classroom action research methods. The observation results showed an increase from cycle I to cycle II, reaching the high category between 65% to 84%. In cycle I, student motivation was 65.52%, increasing to 86.25% in cycle II, in a very high score range. There was an increase in student learning motivation by 20.73% from cycle I to cycle II.In conclusion, the application of demonstration methods is effective in increasing student learning motivation, both individually and classically. This is evident from the increase in the percentage of student learning motivation from 65.52% (cycle I) to 86.25% (cycle II), which is in the very high score range. Thus, it can be concluded that the demonstration method is effective in increasing students' motivation to learn mathematics.